New Water-Soluble Cytokinin Derivatives and Their Beneficial Impact on Barley Yield and Photosynthesis - Klos, Dardan; Dušek, Michal; Samol'ová, Erika; Zatloukal, Marek; Nožková, Vladimíra; Nesnas, Nasri; Plačková, Lenka; Koprna, Radoslav; Spíšek, Zdeněk; Vylíčilová, Hana; Plíhal, Ondřej; Doležal, Karel; et al. (Journal of agricultural and food chemistry, 2022)
Solubility of growth regulators is essential for their use in agriculture. Four new cytokinin salts─6-benzylaminopurine mesylate (1), 6-(2-hydroxybenzylamino)purine mesylate (2), 6-(3-hydroxybenzylamino)purine mesylate (3), and 6-(3-methoxybenzylamino)purine mesylate (4)─were synthesized, and their crystal structures were determined to clarify structural influence on water solubility. The mesylates were several orders of magnitude more water-soluble than the parent CKs. The new salts significantly reduced chlorophyll degradation and impairment of photosystem II functionality in barley leaf segments undergoing artificial senescence and had pronounced effects on the leaves' endogenous CK pools, maintaining high concentrations of functional metabolites for several days, unlike canonical CKs. A foliar treatment with 1 and 3 increased the harvest yield of spring barley by up to 8% when compared to treatment with the parent CKs while also increasing the number of productive tillers. This effect was attributed to the higher bioavailability of the mesylate salts and the avoidance of dimethyl sulfoxide exposure.
Keywords: photosystem; crystal structure; cytokininy; methansulfonáty; soli; voda; Mesylates; Water; antisenescence; solubility; Plant Leaves; endogenous cytokinins; photosynthesis influence; Photosynthesis; Cytokinins; grain yield; mesylates; Salts; bioavailability; spring barley; Hordeum; fotosyntéza; ječmen (rod); listy rostlin; cytokinin